2012
DOI: 10.1177/1078087412465401
|View full text |Cite
|
Sign up to set email alerts
|

Place and Crime

Abstract: Standard sociology and criminology have not been sufficiently sensitive to the unique characteristics that places have. It has been implicitly assumed that one place (be it a neighborhood, census track, or metropolitan area) is interchangeable with another, given certain demographic and economic variables. This article attempts to recast environmental criminology within a sociological framework known as the “sociology of place.” The unequal spatial distribution of crime makes it an ideal candidate for analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
(26 reference statements)
1
13
0
1
Order By: Relevance
“…The prominence of social ties as an indicator of feelings of safety and security in our findings most notably corroborate the arguments made by Kim et al (2013), contending that a distinction between the concepts of space and place help in the understanding of spatial factors contributing to crime, and by extension, perceptions thereof. Physical features associated with any given locale (space), argue Kim et al (2013), do not contribute as effectively to the understandings of crime and safety as do the social and emotional ties that form in a physical setting (place). Similarly, in the present study, students' feelings of safety in school were described as being connected to the presence of supportive and encouraging teachers and school administrators whom the students turned to in times of distress.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The prominence of social ties as an indicator of feelings of safety and security in our findings most notably corroborate the arguments made by Kim et al (2013), contending that a distinction between the concepts of space and place help in the understanding of spatial factors contributing to crime, and by extension, perceptions thereof. Physical features associated with any given locale (space), argue Kim et al (2013), do not contribute as effectively to the understandings of crime and safety as do the social and emotional ties that form in a physical setting (place). Similarly, in the present study, students' feelings of safety in school were described as being connected to the presence of supportive and encouraging teachers and school administrators whom the students turned to in times of distress.…”
Section: Discussionsupporting
confidence: 88%
“…While it is suggested that student achievement increases in schools that have been physically renovated (Uline & Tschannen-Moran, 2008), creating new or improved schools does not necessarily help address the causes of violence within the school setting and across the community (Lipman, 2008). This may be a result of conflating the concepts of space and place in planning and executing revitalization initiatives where improvements in "space"-that is, the physical characteristics of a given location-are believed to lead to improvements in "place," a term used to refer to the confluence of both the physical and the psychosocial qualities that give meaning to that location (e.g., Kim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Public opinion regarding marginalised groups and state policies also contribute to this process (Desmond et al., 2016). ‘Place’ is a particular zone to be exploited by offenders render the relevant targeted zone a suitable opportunity to establish their authority (Kim et al., 2013). This causal relationship reveals how the extra‐legal governance plays a key role in urban transformation (Moser & Rodgers, 2005).…”
Section: Justice‐based Power Vacuums: a Theoretical Concept To Explor...mentioning
confidence: 99%
“…Desde la aparición y uso masivo de los SIG a finales de la década de los noventa 29 , proliferaron los estudios espaciales del delito y de los problemas a éste asociados que son objeto de estudio de la Criminología Ambiental 30 .…”
Section: La Criminología Ambientalunclassified